President's Message - Frenette, Karen (Operating Room Nurses Association of Canada Journal, 2012)
The Operating Room Nurses Association of Canada (ORNAC) is celebrating its 30th anniversary in 2013! For thirty years numerous perioperative Registered Nurses have volunteered their time and energy to ensure safe and efficient care of patients in the perioperative setting as well as to standardize perioperative practices. As I reflect on the history of ORNAC it is evident that the vision of its founding members was remarkable. The first provincial perioperative group, the Operating Room Nurses Association of Quebec, was founded in 1958 under the leadership of Isabelle Adams, Victoire Audit, and Mary Taylor. New perioperative nursing groups were, with guidance from the Quebec leaders, gradually created in other regions across the country. The seed was planted and the need for a national perioperative organization had been identified! In 1983 the Operating Room Nurses Association was launched and its first President was Valerie Shirreff from Ontario.